Implementasi Algoritma Priority Scheduling Pada Sistem Informasi Pemesanan Layanan Fotografi dan Videografi - Anfaisa, Anfaisa Ibnu Danar Dana; Dedi Gunawan (The Indonesian Journal of Computer Science, 2025)
Creative industries in Indonesia are growing rapidly, including photography and videography services. The need for people to capture important moments drives the demand for these services. Agratha Studio, a production house in Surakarta, specializes in photography and videography. However, the ordering process is still done manually, which creates obstacles for customers and studios. This research aims to help Agratha Studio improve services to customers by designing a website-based videography service booking information system. The system is designed with features such as user login and registration, service data management, online ordering, and order management by the admin. This system implements priority scheduling algorithm. The priority scheduling algorithm is a priority-based scheduling algorithm where each scheduling process has a priority number. The development of a website-based videography service ordering information system can help Agratha Studio improve services to customers and increase the efficiency and effectiveness of the ordering process.Regular monitoring of the information system is also conducted to ensure the fulfillment of the objectives underlying the development of this complaint reporting and information system.